Phenomenology yesterday, today, and tomorrow: a proposed phenomenological response to the double challenges of contemporary recovery-oriented person-centered mental health care - Messas, Guilherme; Stanghellini, Giovanni; Fulford, K. W. M. (Bill) (Frontiers in Psychology, 2023)
This paper argues that a dialectical synthesis of phenomenology’s traditional twin roles in psychiatry (one science-centered, the other individual-centered) is needed to support the recovery-oriented practice that is at the heart of contemporary person-centered mental health care. The paper is in two main sections. Section I illustrates the different ways in which phenomenology’s two roles have played out over three significant periods of the history of phenomenology in 20th century psychiatry: with the introduction of phenomenology in Karl Jaspers’ General Psychopathology in 1913; with the development a few years later of structural phenomenological psychopathology; and in the period of post-War humanism. Section II is concerned with the role of phenomenology in contemporary mental health. There has been a turn to phenomenology in the current period, we argue, in response to what amounts to an uncoupling of academic psychiatry from front-line clinical care. Corresponding with the two roles of phenomenology, this uncoupling has both scientific aspects and clinical aspects. The latter, we suggest, is most fully expressed in a new model of “recovery,” defined, not by the values of professionals as experts-by-training, but by the values of patients and carers as experts-by-experience, specifically, by what is important to the quality of life of the individual concerned in the situation in question. We illustrate the importance of recovery, so defined, and the challenges raised by it for both the evidence-base and the values-base of clinical decision-making, with brief clinical vignettes. It is to these challenges we argue, that phenomenology through a synthesis of its twin roles is uniquely equipped to respond. Noting, however, the many barriers to such a synthesis, we argue that in the current state of development of the field, it is by way of a dialectical synthesis of phenomenology’s roles that we should proceed. From such a dialectic, a genuine synthesis of roles may ultimately emerge. We conclude with a note on the wider significance of these developments, arguing that contrary to 20th century stereotypes, they show psychiatry to be leading the way for healthcare as a whole, in developing the resources for 21st century person-centered clinical care.